1995
DOI: 10.1016/0014-5793(95)00688-6
|View full text |Cite
|
Sign up to set email alerts
|

A role for active oxygen species as second messengers in the induction of alternative oxidase gene expression in Petunia hybrida cells

Abstract: Incubation of Petunia hybrida cells with H202 leadsto an increase in alternative oxidase activity measured after 24 h. This increased activity is accompanied by an increase in alternative oxidase protein. A model is presented for the regulation of alternative oxidase protein synthesis in which active oxygen species and especially H202 play a crucial role as second messengers in the signal transducing pathway from the mitochondria to the nucleus. It is proposed that also the induction of the alternative oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(111 citation statements)
references
References 24 publications
(33 reference statements)
10
100
0
Order By: Relevance
“…However, it is not known what role this enzyme serves in other plants, including maize. One compelling idea is that AOX can control the production of free radicals by stabilizing the ratio of reduced ubiquinone to total ubiquinone (Purvis and Shewfelt, 1993;Wagner, 1995;Wagner and Moore, 1997;Millenaar et al, 1998). Indeed, isolated mitochondria were found to produce more H 2 O 2 when the alternative pathway was inhibited (Popov et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not known what role this enzyme serves in other plants, including maize. One compelling idea is that AOX can control the production of free radicals by stabilizing the ratio of reduced ubiquinone to total ubiquinone (Purvis and Shewfelt, 1993;Wagner, 1995;Wagner and Moore, 1997;Millenaar et al, 1998). Indeed, isolated mitochondria were found to produce more H 2 O 2 when the alternative pathway was inhibited (Popov et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…That the Aox1/Ars reporter was not activated when cells were treated with antimycin A or H 2 O 2 was surprising to us given the wealth of previous research from higher plants indicating that Aox1 is strongly induced by both antimycin A (Vanlerberghe and McIntosh 1994) and H 2 O 2 (Wagner 1995). Because of this disparity, we undertook a series of experiments examining Aox1 expression using the more traditional approach of measuring changes in mRNA abundance.…”
Section: Kinetics Of Aox1 Transcript Accumulationmentioning
confidence: 98%
“…In both soybean (Finnegan et al 1997) and Arabidopsis (Saisho et al 1997), each Aox gene shows differential developmental and tissue-specific expression. AOX abundance is transcriptionally controlled with a wide range of stress factors being shown to induce Aox gene expression and/or AOX protein accumulation including chilling (Vanlerberghe and McIntosh 1992), ageing (Hiser and McIntosh 1990), pathogen attack (Simons et al 1999), as well as treating tissues with salicylic acid (Rhoads and McIntosh 1992), H 2 O 2 (Wagner 1995) and the CP inhibitor antimycin A (Vanlerberghe and McIntosh 1994). A common consequence of many of these stresses is that they elevate intracellular ROS levels, which in turn, may represent a common signalling molecule upregulating Aox gene expression (Maxwell et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, high concentration of ROS can lead to phytotoxicity; on the other hand, ROS, particularly hydrogen peroxide (H 2 O 2 ), can be used for acclamatory signaling to activate antioxidant defense systems (Dat et al 2000). Wagner (1995) found that addition of exogenous H 2 O 2 into Petunia hybrida cells resulted Induction of AOX1a gene under salt stress is mediated by H2O2 869 in an increase in both the cyanide-resistant respiration and AOX protein amount, suggesting that H 2 O 2 could be used as secondary messenger in the signal transduction pathway to induce the AOX pathway. However, whether the accumulation of H 2 O 2 under the condition of salt stress would regulate the AOX pathway is still to be determined.…”
Section: Introductionmentioning
confidence: 99%